São Paulo Fashion Week: contributions to the history of fashion in Brazil (ModaPalavra e-periódico, 2024)
This is a historical and exploratory study that intends to collaborate with the existing collection on the history of fashion in Brazil, specifically addressing the origin and genesis of the São Paulo Fashion Week. In order to do so, the trajectory of articulations of important actors in this process is investigated, as well as the socio-historical conditions in which they are intricate, which will stimulate the inception of the mega fashion event in Brazil from the 1990s onwards. In this study, through from the use of bibliographic and documentary research techniques and semi-structured interviews, a chronological overview of the origin and beginning of the genesis of the biggest fashion week in Brazil was reached.
Keywords: fashion history; fashion in Brazil; São Paulo Fashion Week